The Syriac World - King, Daniel; King, Daniel (Taylor & Francis, 2019)
This volume surveys the 'Syriac world', the culture that grew up among the Syriac-speaking communities from the second century CE and which continues to exist and flourish today, both in its original homeland of Syria and Mesopotamia, and in the worldwide diaspora of Syriac-speaking communities. The five sections examine the religion; the material, visual, and literary cultures; the history and social structures of this diverse community; and Syriac interactions with their neighbours ancient and modern. There are also detailed appendices detailing the patriarchs of the different Syriac denominations, and another appendix listing useful online resources for students. The Syriac World offers the first complete survey of Syriac culture and fills a significant gap in modern scholarship. This volume will be an invaluable resource to undergraduate and postgraduate students of Syriac and Middle Eastern culture from antiquity to the modern era.
English
Keywords: Anthropology; Syria; religion; cultures; history; social structures